The impact of preparation parameters on typical attributes of chitosan-heparin nanohydrogels: particle size, loading efficiency, and drug release. (November 2013) - Shahbazi, Mohammad-Ali; Hamidi, Mehrdad
<x xml:space="preserve">Abstract</x> Today, developing an optimized nanoparticle (NP) preparation procedure is of paramount importance in all nanoparticulate drug delivery researches, leading to expanding more operative and clinically validated nanomedicines. In this study, a one-at-a-time experimental approach was used for evaluating the effect of various preparation factors on size, loading, and drug release of hydrogel NPs prepared with ionotropic gelation between heparin and chitosan. The size, loading efficiency (LE) and drug release profile of the NPs were evaluated when the chitosan molecular weight, chitosan concentration, heparin addition time to chitosan solution, heparin concentration, pH value of chitosan solution, temperature, and mixing rate were changed separately while other factors were in optimum condition. The results displayed that size and LE are highly influenced by chitosan concentration, getting an optimum of 63 ± 0.57 and 75.19 ± 2.65, respectively, when chitosan concentration was 0.75 mg/ml. Besides, heparin addition time of 3 min leaded to 74.1 ± 0.79 % LE with no sensible effect on size and release profile. In addition, pH 5.5 showed a minimum size of 63 ± 1.87, maximum LE of 73.81 ± 3.13 and the slowest drug release with 63.71 ± 3.84 % during one week. Although LE was not affected by temperature, size and release reduced to 63 ± 0 and 74.21 ± 1.99% when temperature increased from 25°C to 55°C. Also, continuous increase of mixer rate from 500 to 3500 rpm resulted in constant enhancement of LE from 58.3 ± 3.6 to 74.4 ± 2.59 as well as remarkable decrease in size from 148 ± 4.88 to 63 ± 2.64.